A Statewide EMS Viral Syndrome Pandemic Triage Protocol: 24 Hour Outcomes. (3rd September 2022) - Levy, Matthew J.; Chizmar, Timothy P.; Alemayehu, Teferra; Sidik, Mustafa M.; Garfinkel, Eric; Stone, Roger; Wendell, Jonathan; Vesselinov, Roumen; Margolis, Asa M.; Delbridge, Theodore R.
Abstract: Background: Early during the COVID-19 pandemic, Emergency Medical Services (EMS) systems encountered many challenges that prompted crisis-level strategies. Maryland's statewide EMS system implemented the Viral Syndrome Pandemic Triage Protocol which contained a decision tool to help identify patients potentially safe for self-care at home. Objectives: This study assessed the effects of the Maryland Viral Syndrome Pandemic Triage Protocol and the safety of referring patients for self-care at home. Methods: This is a retrospective statewide analysis of EMS patients from March 19 thru September 4, 2020, who were not transported and had documentation of the Viral Syndrome Pandemic Triage Protocol's decision support tool completed, as well as a random sample of 150 patients who were not transported and did not have documentation of the decision tool. Descriptive statistics were performed as well as a two-stage multivariable logistic regression model for the outcomes of ED presentation within 24 hours and subsequent hospitalization. Results: 301 EMS patients were documented as triaged to home using the protocol and outcomes data were available for 282 (94%). 41(14.5%) patients presented to an ED within 24 hours and 14 (5% of 282) required inpatient hospitalization. Nine (3.2%) patients were subsequently hospitalized with a diagnosis of COVID-19 illness. Of those patients for whom the decision tool was not documented, 35 (23%) had an ED visit within 24 hours and 15 (10%) were hospitalized (p = 0.075). Multivariate logistic regression model results (N = 432) suggest that those with documentation of triage protocol use had some advantage over those patients without documentation. The 95% CIs of the estimated effect of Triage/No Triage protocol documented were wide and crossed the 1.0 limit but overall, all effects Odds Ratios and Adjust Odds Ratios were consistently over 1.0 with the lowest value of 1.3 and the highest value of 2.1. Conclusion: Most patients (95%) who were triaged to self-care at home with home documented decision support tool use did not require hospitalization within 24 hours following EMS encounter and this appears to be safe. Future opportunity exists to incorporate such tools into comprehensive pandemic preparedness strategies along with appropriate follow up and quality improvement mechanisms.